Effect of Biopelleting on Seed Yield of Soybean - SIDDARAJU MK,; RAVI HUNJE,; RAJENDRA PRASAD, (Seed Research, 2026)
The field experiment was conducted to study the influence of biopelleting on seed yield and quality of soybean at the Water and Land Use Management Institute (WALMI) Farm, Dharwad. The fresh seeds of soybean were first pelleted with biofertilizers like RhizobiumSb-120 (@ 25g kg-1 and 50g kg-1) and Pseudomonas striata (@ 25g kg-1 and 50g kg-1) and control (unpelleted) along with maida (Starch gruel @ 60ml kg-1) as a binding material, shade dried and directly used for sowing. Among the seed pelleting with biofertilizers the seeds pelleted with Rhizobium Sb-120 @ 50 g + Pseudomonas striata @ 50g kg-1 seed has recorded highest field emergence (88%), plant height (64.88 cm), number of branches per plant (5.73), number of trifoliate leaves (24.70), less number of days to 50% flowering (38.33), over the unpelleted control seeds (81.33%, 56.87 cm, 4.23, 19.13 and 41.67 days, respectively). Higher seed yield of 21.41 q ha-1 with a 15.98 % increase in case of seed pelleted with Rhizobium Sb-120 @ 50 g + Pseudomonas striata @ 50g kg-1 seed over control. Similarly, maximum number of pods per plant (95.27), pod length (3.69cm), number of seeds per pod (2.91), pod weight per plant (0.338g) and hundred seed weight (13.83g) was registered in seed pelleted with Rhizobium Sb-120 @ 50g kg-1 + Pseudomonas striata @ 50g kg-1 seed over control (71.40, 2.97, 2.57, 0.253g and 12.54g). Biopelleting treatments improved the growth of plant either alone or in combination during early stage of crop with vigorous and stronger root system enabling plants to derive the available soil moisture and nutrients which resulted in enhanced growth and seed yield.